(untitled) (Papeles, 2022)
Currently, one of the most important problems to solve in relation to climate change is the false and lax information that is being disseminated from the information media. The objective of this research, from the perception of teachers in training in Primary Education (University of Valencia, Spain), is to analyze the main information media from which they are receiving information on climate change, the causes and effects that are broadcast, and examine their opinion if the information that are disseminating is manipulated. The results indicate that the main media from which they receive the information are digital (74.1 % social networks; 66.2 % TV; 52.5 % internet). Regarding the causes, human actions stand out (76.3 %) and the consequences: the increase in temperature (37.4 %), extinction species (20.1 %) and melting and rise in sea level (17.3 %). And in relation to the news, more than half have responded that they agree or strongly agree (56.1 %) that the information received are manipulated. Finally, it is worth highlighting the risk that future teachers take most of their knowledge from the digital media due to that they are characterized by not very rigorous information, manipulation, and the diffusion of stereotypes.